Mediating the real: Treme's activated aesthetic. (September 2019) - Moylan, Katie
This article explores how Treme (HBO 2010–2013) deploys reflexive aesthetic strategies to produce a critique of governmental and municipal corruption and negligence following Hurricane Katrina. Set and filmed in New Orleans, Treme negotiates additional complex layers given that many events referenced are real. The series reworks normative representations of New Orleans typified by an overdetermined authenticity in a reflexive interrogation of recent experience and historical memory. I argue Treme develops an 'activated aesthetic' through two textual strategies: opening credit sequences and 'televisual moments', mobilising these aesthetic devices to develop a complex, explicitly politicised representation of post-Katrina New Orleans.